Bantuan Hukum Cuma-Cuma Bagi Tersangka yang Tidak Mampu Pada Tingkat Penyidikan - Rio Saputra; Mokhammad Najih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
Suspects have the right to obtain legal assistance, especially for suspects who are classified as economically disadvantaged in accordance with Article 56 of the Criminal Procedure Code (KUHAP). The facts show that there are many irregularities in the implementation of legal aid, therefore it is necessary to know about the implementation of free legal aid for suspects who are incapacitated at the level of investigation and the factors that become obstacles in the implementation of legal aid. This legal research is an empirical legal research and this research is descriptive in nature. The data used are primary data and secondary data. The techniques used to collect data were document study techniques and interview techniques. Inhibiting factors affecting the implementation of free legal aid for suspects who are unable at the level of investigation can be classified and differentiated into 3 factors, namely, legal substance, legal structure, and legal culture).Keywords: Legal Aid, Criminal Cases